Gross Primary Productivity of Four European Ecosystems Constrained by Joint CO2 and COS Flux Measurements. Issue 10 (21st May 2019) - Spielmann, F. M.; Wohlfahrt, G.; Hammerle, A.; Kitz, F.; Migliavacca, M.; Alberti, G.; Ibrom, A.; El‐Madany, T. S.; Gerdel, K.; Moreno, G.; Kolle, O.; Karl, T.; et al.
Abstract: Gross primary productivity (GPP), the gross uptake of carbon dioxide (CO2 ) by plant photosynthesis, is the primary driver of the land carbon sink, which presently removes around one quarter of the anthropogenic CO2 emissions each year. GPP, however, cannot be measured directly and the resulting uncertainty undermines our ability to project the magnitude of the future land carbon sink. Carbonyl sulfide (COS) has been proposed as an independent proxy for GPP as it diffuses into leaves in a fashion very similar to CO2, but in contrast to the latter is generally not emitted. Here we use concurrent ecosystem‐scale flux measurements of CO2 and COS at four European biomes for a joint constraint on CO2 flux partitioning. The resulting GPP estimates generally agree with classical approaches relying exclusively on CO2 fluxes but indicate a systematic underestimation under low light conditions, demonstrating the importance of using multiple approaches for constraining present‐day GPP. Plain Language Summary: Plants are Earth's biggest contributor for cleaning the atmosphere of carbon dioxide and remove around one quarter of the carbon dioxide emitted by humans each year. However, this contribution cannot be measured directly and has to be inferred or modelled on the basis of related parameters. This introduces large uncertainties, which in turn undermine our ability to accurately create future climate scenarios. Recent research revealed that the trace gas carbonyl sulfide is taken up by plants in a very similar way as carbon dioxide and offers us an additional way of quantifying the carbon dioxide uptake by photosynthesis. Here we use joint measurements of the carbon dioxide and carbonyl sulfide exchange to infer plant carbon dioxide uptake, demonstrating the advantage of using multiple approaches. We apply our method at four major European ecosystems and show that previous approaches, based solely on carbon dioxide, may have underestimated the plant carbon dioxide uptake. Key Points: Traditionally gross primary productivity is inferred from ecosystem‐scale CO2 flux measurements The proposed joint assimilation of CO2 and COS flux measurements avoids the need to specify the leaf relative uptake rate of COS a priori The additional information content of ecosystem‐scale COS flux measurements increases inferred gross primary productivity estimates